A Machine‐Learning‐Based Bibliometric Analysis of Cell Membrane‐Coated Nanoparticles in Biomedical Applications over the Past Eleven Years. Issue 4 (22nd February 2023) - Zhang, Yiyin; Jin, Shengxi; Li, Duguang; Chen, Guoqiao; Chen, Yongle; Xia, Qiming; Mao, Qijiang; Li, Yiling; Yang, Jing; Fan, Xiaoxiao; Lin, Hui
Abstract: Cell membrane encapsulation is a growing concept in nanomedicine, for it achieves the purpose of camouﬂage nanoparticles, realizing the convenience for drug delivery, bio‐imaging, and detoxification. Cell membranes are constructed by bilayer lipid phospholipid layers, which have unique properties in cellular uptake mechanism, targeting ability, immunomodulation, and regeneration. Current medical applications of cell membranes include cancers, inflammations, regenerations, and so on. In this article, a general bibliometric overview is conducted of cell membrane‐coated nanoparticles covering 11 years of evolution in order to provide researchers in the field with a comprehensive view of the relevant achievements and trends. The authors analyze the data from Web of Science Core Collection database, and extract the annual publications and citations, most productive countries/regions, most influential scholars, the collaborations of journals and institutions. The authors also divided cell membranes into several subgroups to further understand the application of different cell membranes in medical scenarios. This study summarizes the current research overview in cell membrane‐coated nanoparticles and intuitively provides a direction for future research. Abstract : This article presents a literature analysis of cell membrane‐coated nanoparticles covering 11 years of evolution based on the data from the Web of Science Core Collection, including the annual publications and citations, most productive countries/regions, most influential scholars, the collaborations of journals and institutions. It gives a current research overview in this field and intuitively provides a vision for researchers.